The role of ICTs' in field supervision of undergraduate students at Makerere University: an activity theory system perspective - Okumu, Tito Oyana (School of Education, 2015)
This research investigates how Information and Communication Technologies (ICT) tools mediate in field supervision of undergraduate students. The research used Activity Theory systems to show that good supervisory practices lead to expansive learning. The study conducted over a two year period of eight weeks each, focussed on nine supervisors, students and administrators in the international programme (summer for the Western Countries) is organised by the College of Veterinary Medicine and Bio-Security of Makerere University. The students undertake field attachment and are supervised using various ICT tools. The research used qualitative methods and was grounded in Activity Theory. Data was collected through interviews, their participation and discussion in the Learning Management Systems (LMS) and the social media network (Facebook & Diigo) and through various feedback reports either from the supervisors or from the students to collect as much information as possible so as to understand the role ICT plays in this process. The research found that while ICT tools mediate in field supervision of undergraduate students through aggregation of multiple experiences and by providing a virtual proximity in the supervisory process. It also found that there are barriers in its usage which need to be addressed when doing so. These included; internet access and availability as key, power outages, and technical knowhow were also mentioned. The research further found that lack of adequate ICT tools to be used in the field, skills and at times failure to credit the source of content hindered its effectiveness. This inevitably creates lack of consistence in the way they are used. The research, therefore, concludes that there is need for a holistic approach to address the problem of barriers and usage so as to have a comprehensive implementation plan for the use of ICT in the supervisory process. This will assist supervisors in integrating them in their practice.